Evolution, Temporality, and Ethics: On Kierkegaard’s Surprising Relevance to Eco-Theology - Klassen, Justin D. (Journal for the Study of Religion, Nature and Culture, 2018)
Christian eco-theologians often focus significant critical attention on anthropocentric accounts of religious faith in which ‘the relation between God and the world is narrowed to God and the individual' (McFague 2008: 68). Some mention Søren Kierkegaard by name as a villain in this respect since his work is fixated on the human being's relation to God in the context of temporality and pays little attention to the physical world. I argue that eco-theologians are nonetheless writing a bright future for Kierkegaardian religious ethics precisely by embracing the insight of evolutionary biology that matter itself is historical. Stemming from an awareness of matter's inherent dynamism, eco-theological attempts to reconcile religious commitments with contemporary science engender ethical recommendations of openness to life's uncharted future. Kierkegaard's insights into the challenges of relating to temporal uncertainty therefore gain a surprisingly concrete ethical relevance in light of evolutionary science.